The Role of Tour Leaders in Providing Comfort for Umrah Pilgrims at Pt Bina Insani Madinah (BIM Group) Tour & Travel - Ulima Febriani; Achmad Syarifudin; Emi Puspita Dewi (Universitas Muhammadiyah Palu, 2026)
This research is entitled